"First Korean Philosophers" on Philosophy. (May 2015) - Kang, Young Ahn
Philosophy as an academic discipline was introduced to Korea at the end of the 19th century. Philosophical education and professional research did not begin, however, until the 1920s. The first institution in which Koreans could study philosophy as a major at college level was Keijō Imperial University, which was founded by the Japanese in 1924 in Seoul, Korea. The first graduates from this school produced their research in Korean and contributed to the settlement of philosophy on the Korean peninsula. They were joined by Koreans who had returned from study in Austria, Germany, France, and the United States. I call these the "first Korean philosophers." In order for an individual to belong to this group, three conditions had to be met: first, he or she should have studied philosophy as a major at college level; second, he or she should have read Western philosophical texts in original or in translation; third: he or she should have written a treatise in the contemporary Korean language. Against this background, I am going to deal with three questions. The first question concerns their attitude towards philosophy. The second question concerns their conception of philosophy. The third question concerns the method of doing philosophy. Through this study, I have shown that the first Korean philosophers foreshadowed the struggle between the Marxist and liberal understandings of the world and of humanity, even though they lived in the time of Japanese occupation.